Back Cover: Hit Identification of a Novel Dual Binder for h‐telo/c‐myc G‐Quadruplex by a Combination of Pharmacophore Structure‐Based Virtual Screening and Docking Refinement (ChemMedChem 16/2016). (19th August 2016) - Rocca, Roberta; Costa, Giosuè; Artese, Anna; Parrotta, Lucia; Ortuso, Francesco; Maccioni, Elias; Pinato, Odra; Greco, Maria Laura; Sissi, Claudia; Alcaro, Stefano; Distinto, Simona; Moraca, Federica
Abstract : The back cover picture shows a high‐throughput in silico screening of commercial libraries from several different vendors by means of a combined structure‐based pharmacophore model approach followed by docking simulations. The compounds selected by the virtual screening procedure were then tested for their ability to interact with human telomeric G‐quadruplex folding by circular dichroism, fluorescence spectroscopy, and fluorescence intercalator displacement. Our workflow was successful in retrieving a novel promising ligand, characterized by a peculiar chemical scaffold, able to well stabilize both human telomeric and c‐myc promoter G4 structures. More information can be found in the Full Paper by Giosuè Costa et al. onpage 1721 in Issue 16, 2016 (DOI:10.1002/cmdc.201600053 ).